Pengaruh Stimulasi Kognitif terhadap Tingkat Pengetahuan tentang Penyakit Tuberkulosis Paru Pasien Rawat Inap di Rumah Sakit Paru Jember (The Effect of Cognitive Stimulation on the Level of Knowledge about the Pulmonary Tuberculosis in-patient at Jember - Moh Halim Mukhlasin; Anisah Ardiana; Roymond H Simamora (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Cognitive stimulation is one of the options that influence the level of knowledge. The intention is to provide information in order to improve the knowledge and thus, leads to the changes on behavior. This research examines the effect of cognitive stimulation on the level of knowledge of the pulmonary tuberculosis in-patient. This research employs one group pretest-posttest design through the help of purposive sampling collection technique. The number of sample involved in this research is 18 individuals. The data analysis is performed using the Spearman’s correlation test. The result of the analysis generated the r value of 0.559 which means strongly and positively correlated. The bivariate testing results in the p value of (0.016)<α(0.05), meaning that the effect of the cognitive stimulation on the patient’s level of knowledge exists. It is suggested that the health care services optimizes the counseling sessions conducted to patients and their families by employing the cognitive stimulation aimed at improving the patient’s level of knowledge as well as their compliance in taking their medication to help recover from the pulmonary tuberculosis, respectively. Keywords: Cognitive Stimulation, Knowledge, Pulmonary Tuberculosis